2017
DOI: 10.1111/jcmm.13208
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐122 modification enhances the therapeutic efficacy of adipose tissue‐derived mesenchymal stem cells against liver fibrosis

Abstract: Mesenchymal stem cell (MSC) transplantation alone may be insufficient for treatment of liver fibrosis because of complicated histopathological changes in the liver. Given that miR‐122 plays an essential role in liver fibrosis by negatively regulating the proliferation and transactivation of hepatic stellate cells (HSCs), this study investigated whether miR‐122 modification can improve the therapeutic efficacy of adipose tissue‐derived MSCs in treating liver fibrosis. MiR‐122‐modified AMSCs (AMSC‐122) were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
145
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 44 publications
1
145
0
1
Order By: Relevance
“…Genetic modification of ADSCs with therapeutic genes was also proved to increase the therapeutic potential of the stem cells . The microRNA‐21 plays critical roles in the regulation of a variety of skin fibrosis, which hold great potential for new diagnostic and therapeutic options for wound remodelling and maturation . The present study demonstrates that miR‐21 modification in ADSCs via lentiviral transfection improved the therapeutic potential of MSCs for urethral wound healing.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Genetic modification of ADSCs with therapeutic genes was also proved to increase the therapeutic potential of the stem cells . The microRNA‐21 plays critical roles in the regulation of a variety of skin fibrosis, which hold great potential for new diagnostic and therapeutic options for wound remodelling and maturation . The present study demonstrates that miR‐21 modification in ADSCs via lentiviral transfection improved the therapeutic potential of MSCs for urethral wound healing.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, many studies have tried to increase the repair performance of transplanted MSCs via various intervention methods, including gene modification and biomaterials‐based tissue engineering approaches. In particular, increasing evidences proved that microRNAs (miRNAs)‐based gene modification of MSCs is proved to have great potential for regenerative medicine …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a follow‐up study that built upon these initial findings found that the >1000 kDa fraction of the conditioned medium contained 50 to 100 nm sized particles that were positive for the EV markers, CD9, CD81, and Alix . Likewise, the EVs generated by MSCs were also shown by different groups to be able to recapitulate the therapeutic benefits of the conditioned medium using a variety of disease models (Figure , left side), such as renal ischemia‐reperfusion injury, stroke, and liver fibrosis …”
Section: Introductionmentioning
confidence: 94%
“…Mesenchymal stem cells (MSCs) are the most widely used cell type for cell transplantation‐based treatments, because of their ability to differentiate into multiple lineages, as well as the ease in which they can be isolated from different tissue sources and propagated . MSCs derived from bone marrow, adipose tissue, muscles, and ESCs are currently being used to treat various diseases and conditions, such as myocardial ischemia, stroke, and musculoskeletal disease, with the idea being that the transplantation of MSCs near the sites of damaged tissue results in their differentiation and reconstitution of the tissue, such that it regains functionality. For example, percutaneous injection of bone marrow‐derived MSCs into the damaged myocardium in a pig model of myocardial ischemia reduced the extent of necrosis, promoted the regeneration of contractile myocardium, and improved overall cardiac function …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation